How we implemented team-based learning for postgraduate doctors. (March 2014) - McMullen, Isabel; Cartledge, Jonathan; Finch, Emily; Levine, Ruth; Iversen, Amy
Abstract Background: Team-based learning (TBL) has been shown to improve knowledge, teamwork and interactivity in medical school settings. There are fewer reports of its use with postgraduate doctors. We report on our experience of using TBL with residents. What we did: We converted a didactic module of lectures into a TBL module for 44 psychiatry residents. This involved training faculty, orientating residents, writing TBL materials, delivering and evaluating the module. On the basis of the positive evaluations we aim to introduce more TBL. Conclusions: TBL can be successfully introduced into a residency training programme. Tips for implementation include: involve a TBL expert and provide experiential training for faculty; hold an orientation session for residents; and provide individual and team incentives to reinforce pre-class preparation and promote engagement with TBL. Avoid underestimating the effort involved in converting lecture-based teaching into TBL and do not assign excessive pre-session assignments.